2015
DOI: 10.1002/pc.23753
|View full text |Cite
|
Sign up to set email alerts
|

Compression molding of Carbon/Polyether ether ketone composites: Squeeze flow behavior of unidirectional and randomly oriented strands

Abstract: Compression molding of randomly oriented strands (ROS) of thermoplastic composite is a new process that enabled the formation of complex shapes with high fiber volume fraction. During compression molding of ROS, several deformation mechanisms occurred. This article focused on the macroscopic squeeze flow mechanism. It ruled how the material will flow and fill intricate features of the mold. The squeeze flow behavior under large strain was investigated for Unidirectional (UD) and ROS. An experimental characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…The absence of a similar reduction for swept angular frequency tests may be related to the fact that these tests began at high value of ω (628 rad/s). The stabilisation of thickness reduction in the 313 kPa, 10 rad/s tests, after ∼4 min, can be explained by increased sample area, which reduces applied pressure below σy, as explained in Picher-Martel et al. 39 for similar behaviour of CF/PEEK randomly oriented strand material. Assuming CF/PEEK is incompressible, calculation of the associated increase in sample width leads to a more refined estimation of σy 225 kPa.…”
Section: Discussionmentioning
confidence: 65%
“…The absence of a similar reduction for swept angular frequency tests may be related to the fact that these tests began at high value of ω (628 rad/s). The stabilisation of thickness reduction in the 313 kPa, 10 rad/s tests, after ∼4 min, can be explained by increased sample area, which reduces applied pressure below σy, as explained in Picher-Martel et al. 39 for similar behaviour of CF/PEEK randomly oriented strand material. Assuming CF/PEEK is incompressible, calculation of the associated increase in sample width leads to a more refined estimation of σy 225 kPa.…”
Section: Discussionmentioning
confidence: 65%
“…3 However, only a limited number of studies found in the literature discuss processability and mechanical properties of these materials. A new multi-disciplinary study [4][5][6][7][8] is being conducted to systematically evaluate, characterize and model the moulding process and mechanical properties of composites manufactured from carbon/polyetherether-ketone (PEEK) ROS.…”
Section: Introductionmentioning
confidence: 99%
“…The selection of the process parameters was based on the result of the DSC test, the range of settings recommended by the prepreg supplier and other empirical parameters. 6,16 The laminates were heated from room temperature (approximately 25°C) to moulding temperatures (i.e. 360°C, 380°C and 440°C) at an average rate of 5°C min −1 and then the moulding pressures were adjusted to the set values (1, 2 and 3 MPa) within 2 min.…”
Section: Experiments and Testingmentioning
confidence: 99%